Expression of matrix metalloproteinase-8 gene in fixed orthodontic patients - Susilowati Susilowati; Mansjur Nasir; Imam Mudjari; Thalca Hamid (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Orthodontic treatment with fixed appliance produces structural and biochemical changes and breaking the balance between the synthesis and the breakdown of the collagen in the periodontium. Matrix metalloproteinase-8 (MMP-8) plays an important role in the remodeling of periodontal ligament during orthodontic movement. Purpose: The purpose of this study was to observe the expression of MMP-8 gene in the gingival crevicular fluid (GCF) of fixed orthodontic patients. It is expexted that the result can be used as a reference to decide the proper time for elastomeric chain to be reactivated. Methods: Orthodontic fixed appliances were placed on 8 patients and elastomeric chains exerting 75 grams were attached to produce canine distalization. GCF samples were collected from the distal side of upper canines before force application, 1-, 2-, 3-, and 4 weeks after application consecutively. The samples were analyzed by using RT-PCR. Statistical analyses used were univariate analysis and Mann-WhitneyU test. Results: The expression of MMP-8 in the GCF at t0 was 31.3% but the force application elevated its expression to 65.6% at t1, and then decreased continously at t2, t3, and t4. There was no statistically significant difference of MMP-8 gene expression between t0 and t3. Conclusion: The highest level of MMP-8 gene expression due to orthodontic forces was occured in the first week, but it declined continously in the following weeks. The proper time to reactivate an elastomeric chain was 3 weeks after application.Latar belakang: Perawatan ortodontik dengan peranti cekat menghasilkan perubahan-perubahan stuktural dan biokimiawi pada jaringan periodontal dan mengganggu keseimbangan antara sintesis dan pemecahan kolagen pada periodonsium. Matrix metalloproteinase-8MMP-8 memainkan peran yang penting dalam remodeling ligamentum periodontal selama pergerakan gigi ortodontik. Tujuan: Tujuan dari penelitian ini ialah untuk mengamati ekspresi gen MMP-8 dalam cairan krevikuler gingiva (GCF) dari pasien ortodontik cekat. Diharapkan bahwa hasil penelitian ini dapat digunakan sebagai acuan untuk menentukan waktu yang paling tepat untuk mengaktivasi kembali rantai elastomer. Metode: Peranti ortodontik cekat dipasang pada 8 pasien dan rantai elastomer dengan kekuatan 75 gram dipasang untuk menarik gigi kaninus ke distal. Sampel GCF dikumpulkan dari bagian distal gigi kaninus atas berturut-turut sebelum aplikasi gaya, 1-, 2-, 3-, dan 4 minggu setelah aplikasi. Sampel dianalisis dengan menggunakan RT-PCR. Analisis statistik yang digunakan adalah analisis univariat dan uji Mann-Whitney U. Hasil: Ekspresi gen MMP-8 di dalam GCF pada t0 adalah 31.3%, tetapi pemberian tekanan menaikkan ekspresinya menjadi 65,6% pada t1 dan kemudian menurun secara kontinyu pada t2, t3, dan t4. Tidak ada perbedaan yang bermakna secara statistik antara ekspresi gen MMP-8 pada to dan t3. Kesimpulan: Tingkat ekspresi tertinggi dari gen MMP-8 akibat tekanan ortodontik terjadi pada minggu pertama, tetapi kemudian menurun pada minggu-minggu berikutnya. Waktu yang paling tepat untuk mengaktivasi kembali rantai elastomer adalah 3 minggu setelah aplikasi.